Clinical Significance of Peripheral Blood PCA3 Gene Expression in Early Diagnosis of Prostate Cancer - Chunhua, Lin (Transl Oncol, 2018)
Prostate cancer antigen 3 (PCA3) is one of the most promising genes currently investigated as a specific tumor biomarker for the diagnosis of prostate cancer. The purpose of this study was to investigate PCA3 gene expression in peripheral blood of prostate cancer (PCa) and benign prostate hyperplasia (BPH), and further to assess its clinical significance. We determined the copies of PCA3 mRNA in peripheral blood of PCa and BPH from 115 samples (PCa, n = 78; BPH, n = 37) using a quantitative reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) with TaqMan assay. The sensitivity and specificity of PCA3 for the diagnosis of prostate cancer was compared with that of prostate-specific antigen (PSA) by receiver operating characteristic (ROC) curve analysis. To evaluate the association between PCA mRNA and disease progression, we analyzed PCA3 levels in connection with Gleason score and TNM stage of PCa. The clinical data revealed that expression of PCA3 gene was significantly higher in PCa than in BPH. Moreover, PCA3 mRNA was significantly higher in PCa patients with a Gleason score ≥8 than in those with a Gleason score ≤7 (P < .01). The results showed that the area under the curve (AUC) was 0.790, 0.606, and 0.620 for the copy number of PCA3, PSA level, and significantly free PSA (fPSA) level, respectively. Increased PCA3 in peripheral blood is correlated with PCa, and the detection of PCA3 may significantly reduce adverse screening outcomes. PCA3 gene expression in peripheral blood had a promising clinical application in the early diagnosis of PCa.